Predicting adoption of location-based social media service in travel decisions - Tong, Xiayu; Bao, Haijun; Chong, Alain Yee Loong (Inderscience, 2016)
Advances in location-acquisition and mobile communication technologies have empowered people to use location-based social media. However, the technologies are relatively new, and there is little literature on the relevant factors determining location-based social media adoption. We examine if the online information reviews information can predict users' location-based social media usage for travel planning. The results of this study will be useful for location-based social media providers in formulating appropriate marketing strategies and in developing applications that will attract more users.